How the Attitude of Acceptance, Enthusiasm and Learning through Motivation Affects Brain Development in Children with Autism: A Literature Review (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Research on the autism spectrum (AS) has expanded tremendously over the last two decades with exciting insights into underlying neurobiology. Neuroplasticity, the remarkable ability of the brain to form new connections as a result of experience, is not limited to specific parts of the brain nor does it have a time limit meaning that growth and learning are on-going processes. In this review we explore the impact of the attitude of acceptance, enthusiasm and learning through motivation on brain development in children on the AS. The first part of the review focusses on the impact of attitude on social, emotional and cognitive development, while the second part focusses on the impact of attitude on brain biology.